Immobilized poly(aryleneethynylene) pH strips discriminate different brands of cola - Bender, Markus; Bojanowski, Maximilian; Seehafer, Kai; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
Fluorescent, water-soluble poly(p-aryleneethynylene)s (PAE) were immobilized on commercially available nylon membranes by using a slot plotter, creating fluorescent, barcode-like sensor strips. Digital imaging by using a standard digital camera, before and after immersion of the strips in buffers of different pH, displays a unique color for each pH value. Statistical evaluation, multivariate analysis of variance (MANOVA) and principal component analysis (PCA), of the acquired data revealed that the immobilized PAEs are superior to the identical fluorophores when dissolved. The pH sensor array discriminates 20 different brands of commercial-cola soft drinks through differences in pH and colorant-PAE interactions.
Gesehen am 11.03.2020